Ethical Aspects of Organ Donation After Circulatory Death. Issue 5 (October 2015) - St. Louis, Erik K.; Sharp, Richard R.
Abstract : ABSTRACT: Neurologists should be familiar with the process and ethical aspects of organ donation. While most neurologists understand the steps involved in organ procurement following brain death, the controversial practice of organ donation after circulatory death (also referred to as non–heart-beating organ donation) is less familiar but increasingly frequent. This article presents a hypothetical case of a patient with a devastating neurologic injury and a poor prognosis for meaningful recovery and discusses the ethical considerations underlying donation after circulatory death, the general procedure of donation after circulatory death, and ethical controversies associated with this practice.